FACTORS ASSOCIATED WITH PNEUMONIA AMONG UNDER-FIVE CHILDREN IN HOUSEHOLDS WITH SMOKERS AROUND GETASAN HEALTH CENTER: Faktor yang Berhubungan dengan Pneumonia Balita pada Keluarga Perokok di Wilayah Puskesmas Getasan - A'syifa, Nurul; Hestiningsih, Retno; Yuliawati, Sri; Sutiningsih, Dwi (Universitas Airlangga, 2026)
Background: Pneumonia is a severe lung infection that affects the respiratory system and continues to pose a major global health issue for children under five. In the service area of Getasan Public Health Center—where 66% of households have active smokers—the annual incidence of pneumonia in children under five is consistently higher than other primary healthcare centers in Semarang Regency. This pattern highlights the influence of environmental factors, especially exposure to cigarette smoke. Purpose: This study examines the factors associated with pneumonia among children under five from smoker households. Methods: A case-control design was involved, involving 57 respondents from households with active smokers. Data were collected through a structured interview using a standardized questionnaire. Analytical methods applied in this study comprised univariate, bivariate, and multivariate tests. Results: Duration of exposure to cigarette smoke (p=0.01; AOR=5.80; 95% CI=1.50–22.44) and household cleaning habits (p=0.02; AOR=5.56; 95%CI=1.38–22.38) showed statistically significant results. Conclusion: Prolonged exposure to cigarette smoke and poor household cleaning habits were strongly linked to pneumonia among children under five in smoker households. Strengthening health education and preventive programs at the community level is recommended to promote smoke-free environments and safeguard child health.